2015
DOI: 10.1016/j.solmat.2015.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Shape-stabilized phase change composite by impregnation of octadecane into mesoporous SiO

Abstract: a b s t r a c tWe developed shape-stabilized phase change composites (PCCs) for building materials with high heatstorage density by vacuum impregnation of the phase change material (PCM) octadecane into mesoporous SiO 2 . We examined the effects of the average pore size of mesoporous SiO 2 on the melting point and latent heat of the PCCs. Cyclic tests of melting and freezing were performed to evaluate leakage and degradation of the PCCs. The thermophysical properties of the PCCs were measured by differential s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 34 publications
2
54
0
Order By: Relevance
“…In practice, fatty acids are impregnated into porous building materials to prepare form-stable composites. Considering the strong capillary force generated on a pore with small diameter [9], a variety of natural porous materials with smaller pores such as expanded perlite [10,11], attapulgite [12] and halloysite [13], are frequently used to avoid the leakage of fatty acids during melting process. Additionally, the low thermal conductivity of fatty acids poses a challenge for their applications.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, fatty acids are impregnated into porous building materials to prepare form-stable composites. Considering the strong capillary force generated on a pore with small diameter [9], a variety of natural porous materials with smaller pores such as expanded perlite [10,11], attapulgite [12] and halloysite [13], are frequently used to avoid the leakage of fatty acids during melting process. Additionally, the low thermal conductivity of fatty acids poses a challenge for their applications.…”
Section: Introductionmentioning
confidence: 99%
“…Thereinto, Δ H m, mixture and W SiO2 were the melting enthalpy (210.0 kJ·kg −1 ) of the modified EHS and the mass fraction of SiO 2 in CPCM, respectively. As exhibited in Table , it is evident that the measured melting enthalpies (Δ H m, cpcm ) were slightly lower than the Δ H m, t , which may be attributed to the nonfreezing water layer existing as a part of the physical pore wall between EHS and SiO 2 …”
Section: Resultsmentioning
confidence: 93%
“…As exhibited in Table 3, it is evident that the measured melting enthalpies (ΔH m, cpcm ) were slightly lower than the ΔH m, t , which may be attributed to the nonfreezing water layer existing as a part of the physical pore wall between EHS and SiO 2 . 30,42,43 Besides, the supercooling degrees (ΔT) of CPCMs were also investigated, and the relevant results are also summarized in Table 3. It was obvious that the ΔT of EHS was further decreased after it was composited with SiO 2 .…”
Section: Improvement Of Ehs Supercoolingmentioning
confidence: 99%
“…In recent years, inorganic porous materials such as expanded graphite, expanded perlite, silica, and some polymers, which possess good sorption properties, porous structures, as well as good chemical and thermal stability, have been chosen as shape stabilization matrices. Preliminary studies of porous supports for SSPCMs show that the shape stabilization and phase change properties of SSPCMs closely depend on their average pore size . Goitandia et al demonstrated that conventional macroporous materials had the problem of serious PCM leakage .…”
Section: Introductionmentioning
confidence: 99%